Biomonitoring of Indoor Air Fungal or Chemical Toxins with Caenorhabditis elegans nematodes - Paavanen-Huhtala Sari; Kalichamy Karunambigai; Pessi Anna-Mari; Häkkilä Sirkku; Saarto Annika Tuomela Marja; Andersson Maria A.; Koskinen Päivi J. (MDPI, 2025)
Bad indoor air quality due to toxins and other impurities can have a negative impact on human well-being, working capacity and health. Therefore, reliable methods to monitor the health risks associated with exposure to hazardous indoor air agents are needed. Here, we have used transgenic Caenorhabditis elegans nematode strains carrying stress-responsive fluorescent reporters and evaluated their ability to sense fungal or chemical toxins, especially those that are present in moisture-damaged buildings. Liquid-based or airborne exposure of nematodes to mycotoxins, chemical agents or damaged building materials reproducibly resulted in time- and dose-dependent fluorescent responses, which could be quantitated by either microscopy or spectrometry. Thus, the C. elegans nematodes present an easy, ethically acceptable and comprehensive in vivo model system to monitor the response of multicellular organisms to indoor air toxicity.